Universidade e inovação científica e tecnológica: um estudo patentométrico na Unesp - Pavanelli, Maria Aparecida [UNESP] (2012)
This research aims to quantitatively identify all patents, whether an invention, utility models, trademarks, industrial design and software design within UNESP - Universidade Estadual Paulista, seeking to highlight the most productive researchers, their themes and existing collaborations, both as individual as the institutional framework. From the quantitative data it is sought to describe and analyze the most productive researchers, the partnerships established between them and also the partnerships between the institutions to which they belong. This is appropriate for this research, especially by the needs of knowing and giving visibility to the records of patents at UNESP, considering the lack of such work at the University. As a research procedure, we analyzed the documents provided by UNESP Technology Transfer Office - AUIN, containing a list of patents filed on behalf of UNESP, from 1980 to 2010. They were categorized according to the following types: Patent (PI), utility models (MU), trademarks (TM) and industrial design (ID), all distributed according to the table of areas of Knowledge of CNPq (large area and area): Agricultural Sciences (large area) and Veterinary Medicine (areas), Biological Sciences (large area) and Botany and Microbiology (areas), Exact Sciences and Earth (large area) and Physics, Chemistry, Computer Science, Probability Statistics and Geosciences (areas); Health Sciences (large area) and Pharmacy, Medicine and Dentistry (areas), engineering (large area) and Metallurgical and Materials Engineering and Mechanical Engineering (areas). Stood out the most productive inventors and their respective themes, according to the units and/or college of origin. As search results, considering the total of 114 patent applications, IQ (Institute of Chemistry) at Araraquara had 29 records, the largest number... (Complete abstract click electronic access below)